2020
DOI: 10.1080/10826084.2020.1793368
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Clinical Characteristics of Regular GHB-Users with and without GHB-Induced Comas

Abstract: Background: Gamma hydroxybutyric acid (GHB) has been used recreationally for nearly three decades and its chronic use is frequently associated with serious adverse events including GHB-intoxication with GHB-induced comas. Moreover, despite its low prevalence, the number of individuals with GHB-use disorders is steadily increasing. However, the risk-factors associated with chronic GHB-use or the development of a GHB-use disorders remain poorly understood. Purpose: This study aims to profile two types of GHB-use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
2
6
0
Order By: Relevance
“…Demographic characteristics of cases in this study and patterns in ED presentation day and time are consistent with observations from ambulance data in Victoria [1] and ED presentations in NSW [10] and SA [3]. The median age of 34 years is higher than reported in other studies [30][31][32], and the proportion of female GHBconfirmed cases (n = 24, 53.3%) contrasted with the predominance of males reported in studies with GHB user-groups [14] and ED presentation [12,33,34] and coronial data [2]. Three-quarters of GHB-confirmed ED presentations in our case series occurred on a weekday (Monday to Friday; n = 35, 77.8%), and most commonly between 12:00 and 18:00 h (44.4%).…”
Section: Discussionsupporting
confidence: 88%
“…Demographic characteristics of cases in this study and patterns in ED presentation day and time are consistent with observations from ambulance data in Victoria [1] and ED presentations in NSW [10] and SA [3]. The median age of 34 years is higher than reported in other studies [30][31][32], and the proportion of female GHBconfirmed cases (n = 24, 53.3%) contrasted with the predominance of males reported in studies with GHB user-groups [14] and ED presentation [12,33,34] and coronial data [2]. Three-quarters of GHB-confirmed ED presentations in our case series occurred on a weekday (Monday to Friday; n = 35, 77.8%), and most commonly between 12:00 and 18:00 h (44.4%).…”
Section: Discussionsupporting
confidence: 88%
“…Whether such alterations also occur in recreational GHB-users, particularly in those experiencing multiple GHB-induced comas have been recently investigated by Pereira et al . [ 55 , 106 - 110 ]. For their investigations, they recruited 81 participants equally divided over three groups: (a) chronic users of high GHB doses (≥25 times in preceding two years) with multiple GHB-induced comas (≥4) with or without a GHB-use disorder (GHB-Coma group); (b) regular users of moderate GHB doses that never had a GHB-induced coma (GHB-NoComa group); and (c) a control group of mild polydrug users who never used GHB, since polysubstance use is a common habit among GHB users (No-GHB group).…”
Section: Resultsmentioning
confidence: 99%
“…found that heavy GHB-users who had multiple GHB-induced comas ( i.e . GHB-Coma group) perform worst on verbal memory and self-reported higher levels of anxiety, stress, depression, and impulsivity [ 55 , 106 , 108 ]. Moreover, in fMRI studies using episodic memory, working memory, and emotion processing tasks, the GHB-Coma group showed a compromised capacity to interpret and encode new memories, reduced focus, and problems in interpreting negative emotions compared to the other two groups [ 106 - 108 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical effects become evident as early as 5 min after ingestion, reaching their peak after 30–60 min. GHB can induce a dose-dependent stimulant or sedative effect, adding to its recreational appeal [ 12 ]. This dual effect is associated with euphoria, disinhibition, sensory and sexual arousal at lower doses, evolving into anxiolytic, narcotic and sedative effects and altered states of consciousness at higher doses.…”
Section: Introductionmentioning
confidence: 99%